Distribution, abundance and ecological associations among two species of native mussels (Gonidea angulata and Margaritifera falcata) and one invasive clam species (Corbicula fluminea) in the Columbia River Basin, North America - Nathaniel G. Neal; Stephen M. Bollens; Alexa N. Maine; Timothy D. Counihan; Gretchen Rollwagen-Bollens (Aquatic Sciences, 2026)
Native freshwater mussels are declining globally, thus, determining factors associated with bivalve distribution and abundance is critical for native mussel conservation. In the Columbia River Basin, Gonidea angulata (western ridged mussel) is highly threatened, while Margaritifera falcata (western pearlshell) and the invasive clam Corbicula fluminea (Asian clam) are more common. We conducted 147 snorkel surveys, collected environmental data and performed statistical tests to quantify which variables were significantly associated with presence and abundance of these taxa. Variation in G. angulata presence and/or abundance were best explained by impervious surface proportion and annual air temperatures (mean and maximum). Margaritifera falcata presence and/or abundance were best explained by host fish presence, G. angulata presence, dissolved oxygen, and elevation. Corbicula fluminea presence and/or abundance were best explained by substrate size, impervious surface proportion, and annual air temperatures. Microhabitat and landscape variables explained some variation in bivalve presence and abundance, but the inclusion of watershed as a random effect increased the explanatory value. Consideration of species-specific habitat preferences and watershed-level variation could improve regional management in response to native mussel declines and invasive clam expansion.